Inhaled magnesium versus inhaled salbutamol in rescue treatment for moderate and severe asthma exacerbations in pediatric patients - Michelle Siqueira Debiazzi; Rossano César Bonatto; Fábio Joly Campos; Joelma Gonçalves Martin; José Roberto Fioretto; Maria Letícia das Neves Hansen; Arthur Martins de Araújo Luz; Haroldo Teófilo de Carvalho (Elsevier, 2024)
Objective: To compare the effectiveness of inhaled Magnesium Sulfate associated with Salbutamol versus Inhaled Salbutamol alone in patients with moderate and severe asthma exacerbations. Method: Clinical, prospective and randomized study with patients between 3 and 14 years of age divided into two groups: one to receive inhaled salbutamol associated with magnesium sulfate (GSM), the other to receive inhaled salbutamol alone (GS). The sample consisted of 40 patients, 20 patients in each group. Severity was classified using the modified Wood-Downes score, with values between 4 and 7 classified as moderate and 8 or more classified as severe. Results: Post-inhalation scores decreased both in patients who received salbutamol and magnesium and in those who received salbutamol alone, with no statistically significant difference between the groups. Conclusions: Despite the benefits when administered intravenously, inhalation of the drug alone or in combination did not reduce the severity of the exacerbation.